2003
DOI: 10.1016/s0376-8716(02)00342-3
|View full text |Cite
|
Sign up to set email alerts
|

Income distribution and risk of fatal drug overdose in New York City neighborhoods

Abstract: Accidental drug overdose is a substantial cause of mortality for drug users. Neighborhood-level factors, such as income distribution, may be important determinants of overdose death independent of individual-level factors. We used data from the Office of the Chief Medical Examiner to identify all cases of accidental deaths in New York City (NYC) in 1996 and individual-level covariates. We used 1990 US Census data to calculate the neighborhood-level income distribution. This multi-level case-control study inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
103
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(108 citation statements)
references
References 47 publications
3
103
2
Order By: Relevance
“…CDs are well-defined units, each with an administrative community board, that as such have political and social a priori significance for their residents. (Messner and Tardiff, 1986;Marzuk et al, 1997;Suecoff et al, 1999;Galea et al, 2003a) Examples of these CDs include the Upper West Side in Manhattan and Bedford-Stuyvesant in Brooklyn. These CDs will be referred to as neighborhoods hereafter.…”
Section: Neighborhood Definitionmentioning
confidence: 99%
“…CDs are well-defined units, each with an administrative community board, that as such have political and social a priori significance for their residents. (Messner and Tardiff, 1986;Marzuk et al, 1997;Suecoff et al, 1999;Galea et al, 2003a) Examples of these CDs include the Upper West Side in Manhattan and Bedford-Stuyvesant in Brooklyn. These CDs will be referred to as neighborhoods hereafter.…”
Section: Neighborhood Definitionmentioning
confidence: 99%
“…21,22 Investigators in New York City saw a distinct rise of prescription opioid overdose deaths in affluent, geographically distinct areas in the early 2000s and a subsequent transition to heroin overdose death in those same areas. 23,24 The current characteristics of opioid overdose death in other urban regions in the USA are underexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have investigated demographic, behavioural and drug use related parameters associated to drug-related mortality (Darke & Zador, 1996;Degenhardt, Bucello, Mathers, Briegleb, & Ali, 2011;Fischer et al, 2004;Mathers et al, 2013). Research focusing on social and economic determinants appears to be less prevalent, although previous studies have reported associations between fatal overdoses and poor educational attainment (Arias & Borrell, 1998;Farrell, Neeleman, Griffiths, & Strang, 1996), unemployment (Harlow, 1990;Pasarin, Borrell, & Plasencia, 1999), low income (Pasarin et al, 1999;Torralba et al, 1996), poverty status (Jones et al, 2002;Marzuk et al, 1997;Torralba et al, 1996), living in a neighbourhood presenting important income inequalities (Galea et al, 2003;Nandi et al, 2006), homelessness (Langendam, van Brussel, Coutinho, & van Ameijden, 2001;O'Driscoll et al, 2001), poor psychosocial functioning (Darke & Zador, 1996), social exclusion and poor social support (Farrell et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Davoli et al (1993) published a study that investigated risk factors for drug overdose mortality, including 81 cases and 324 controls, matched on sex and year of birth and found no association with the educational status of victims. Galea et al (2003) (cases) and 453 accidental deaths due to other causes (controls) in various neighbourhoods in New York City. Their results showed increased odds of dying from overdose in neighbourhoods with unequal income distribution.…”
Section: Introductionmentioning
confidence: 99%